Effect of geosynthetic reinforcement creep on the long term performance of an embankment - Karim, M.R.; Gnanendran, C.T.; Lo, S.C.R. (2012)
Geo-synthetic reinforcements are often used to enhance the stability of geotechnical structures such as embankments. These geosynthetic polymers often show significant creep deformational behaviour. In the short-term performance of a geotechnical structure, it may not play a significant role. However, while dealing with the long term behaviour, it is necessary to investigate its effect. In this paper two plane strain fully coupled finite element analysis have been conducted; one with and the other without taking into account of the creep behaviour of geosynthetics. A well documented field case of Leneghans embankment (Geogrid improved wide embankment constructed near Sydney, Australia in 1990s) have been used for this purpose. It is evident from the analyses that though the geosynthetic reinforcements may play a vital role in the performance/stability of an embankment in the early days (during and after construction), its contribution may become insignificant with time and the creep of geo-synthetic may not play a significant role in the long term stability.